‘I haue written here a prayer’: The Making of John Bradford’s Mother’s Prayer - Louise Horton (Janeway JS, 2017)
This article searches for the history of John Bradford’s mother’s prayer by asking how words reported to have been spoken in July 1555 came to be printed nearly thirty years later in Thomas Bentley's The Monument of Matrones. Through renewed analysis of TheMonument’s preface, the article considers the prayer in the context of how Bentley’s anthological practices enabled him to collect sufficient texts to oil the 1600 pages of his seven lamps for wise virgins. Thus, guided by Bentley’s own admission of how he found ‘woorthie paternes’ in ‘excellent and rare works’, the article recovers a previously unrecognised material history for the prayer, and consequently raises complex questions about the formation of authorial identities through the attribution of texts.
Keywords: architecture; Imperialism; Eighteenth Century; Travel Writing; Orientalism; Memory.